2014
DOI: 10.1182/blood-2012-08-450403
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 calcium sensor is required for activation of the phagocyte oxidase during inflammation and host defense

Abstract: Key Points STIM1-mediated calcium entry is critical for neutrophil superoxide release via activation of calcium-sensitive PKCα and PKCβ. STIM1 deficiency results in profound susceptibility to bacterial infection, but also protection in hepatic ischemia/reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 56 publications
4
88
2
4
Order By: Relevance
“…Recent studies revealed that neutrophil NOX2 is important for the activities of phosphatase and tensin homolog (PTEN) and AKT 47 and that SOCE activates PKCa/b, thereby phosphorylating p47 phox during neutrophil activation. 30 However, we found that PTEN activity is reduced in both NOX2 KO platelets and neutrophils after agonist stimulation (supplemental Figure 6) and that there is no difference in PKCa/b phosphorylation between WT and NOX2 KO cells after agonist stimulation or TG-induced SOCE (supplemental Figure 7). Thus, consistent with our recent report demonstrating the importance of AKT2 in Ca 21 signaling during neutrophil activation, 1 these findings provide evidence that AKT signaling regulates ROS-mediated Ca 21 signaling.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies revealed that neutrophil NOX2 is important for the activities of phosphatase and tensin homolog (PTEN) and AKT 47 and that SOCE activates PKCa/b, thereby phosphorylating p47 phox during neutrophil activation. 30 However, we found that PTEN activity is reduced in both NOX2 KO platelets and neutrophils after agonist stimulation (supplemental Figure 6) and that there is no difference in PKCa/b phosphorylation between WT and NOX2 KO cells after agonist stimulation or TG-induced SOCE (supplemental Figure 7). Thus, consistent with our recent report demonstrating the importance of AKT2 in Ca 21 signaling during neutrophil activation, 1 these findings provide evidence that AKT signaling regulates ROS-mediated Ca 21 signaling.…”
Section: Discussionmentioning
confidence: 76%
“…30 However, it remains poorly understood whether NOX2 deletion affects Ca 21 mobilization, which is critical for regulating the function of cell surface receptors. 31 We found that compared with WT platelets, NOX2 KO platelets significantly inhibited intracellular Ca 21 release upon thrombin stimulation ( Figure 6A) but did not alter SOCE in the presence of 2 mM CaCl 2 .…”
Section: Platelet and Neutrophil Nox2 Differentially Modulate Ca 21 Mmentioning
confidence: 99%
“…A previous study demonstrated in an in vivo experiment that STIM1 in neutrophils plays a role in bacterial clearance and is involved in ischemia-reperfusion injury. 5 However, several studies demonstrated differential roles for STIM1 and/or STIM2 depending on the immune cell type. The relative expression levels of both molecules are cell type dependent, indicating distinct functions.…”
mentioning
confidence: 99%
“…In particular, TRPC1 is reportedly associated with cell proliferation, cell migration, enzyme and fluid secretion, normal metabolism in various organ systems, and cancer metastasis (6,10,11). TRPC1 could also form a heteromultimer with Orai1 and stromal interaction molecule 1 (STIM1), which are essential for Ca 2ϩ signaling (12)(13)(14). This interaction may allow the activation of immune ligands (e.g., Toll-like receptors [TLRs]), and thus TRPC channel proteins may play a role in host defense, which has been demonstrated only in the context of lipopolysaccharide (LPS) by regulating cytokine production and inflammatory response.…”
mentioning
confidence: 99%